Effect of gibberellic acid on seed germination and plant development - Cano-Macías, Francisco; Vélez-Chávez, Jean; Vélez-Chávez, Ayrton; Alvarado-Salvador, Ronald (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2025)
Gibberellic acid (GA3) is a plant phytohormone that regulates key processes such as seed germination, cell elongation, flowering, and fruit formation. This systematic review aimed to analyze the effects of GA3 on seed germination, root length, plant height, leaf number, flower number, and yield in various crops. A comprehensive literature search was conducted in the databases covering publications from 2001 to 2025. Inclusion criteria focused on experimental studies conducted in laboratories, greenhouses, or field conditions. A total of 55 studies were selected, including 52 international and 3 national publications. The results indicate that GA3 application increases germination percentage, root elongation, plant height, and leaf production in most evaluated crops. In addition, it promotes an increase in the number of flowers and yield in some species, especially when optimal concentrations are applied. However, high doses may cause adverse effects, such as reduced germination, hormonal imbalances, poor structural development, or decreased quality and yield in certain crops. This review provides an updated synthesis of the physiological responses of different plant species to GA3, highlighting its importance in agriculture while emphasizing the need for proper dosage management according to the species and production objectives.